Conjugal disharmony: a hitherto unrecognised cause of strokes. Issue 6237 (9th August 1980) - Milligan, N; Anderson, M
Abstract : Two women of reproductive age suffered strokes. Neither was taking oral contraceptives, and investigations showed no other causal factors. The radiological findings were characteristic of traumatic internal carotid artery occlusion, but neither patient gave a history of trauma. Only after further inquiry into the patients' social circumstances did it emerge that each had survived an attempt at strangulation by her husband. Such a cause of stroke in young women should be considered when other causes of carotid artery occlusion cannot be identified.